Analisis Hubungan Persentase Ketidakseimbangan Beban terhadap Rugi Daya pada Transformator Distribusi di PT PLN (Persero) ULP Binjai Timur - Alexius Victor Purba; Haris Gunawan; Dino Erivianto (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The distribution transformer is one of the most important components in the electrical power distribution system. Distribution transformers often experience load imbalance issues. One previous study indicated that load imbalance can reach 25.6%, contributing to an increase in power losses. This study aims to analyze the relationship between the percentage of load imbalance and the power losses that occur at PT. PLN (Persero) ULP Binjai Timur. This research was conducted using a quantitative approach by calculating the percentage of load imbalance and the resulting power losses. Data were collected through direct observation, voltage and current measurements, followed by calculations and analysis. The results of the study show that the higher percentage of load imbalance occurred at night, with 12.96%, while during the day it was 10.03%. The power losses were higher at night, amounting to 853.3 watts, while during the day it was 4,386.3 watts. Therefore, it can be concluded that the higher the percentage of load imbalance, the higher the power losses that occur.